What is the burden of submicroscopic malaria in pregnancy in central India?. (February 2015) - Singh, Neeru; Bharti, Praveen K.; Singh, Mrigendra P.; Singh, Rajshree; Yeboah-Antwi, Kojo; Desai, Meghna; Udhayakumar, Venkatachalam; Muniyandi, Malaisamy; Hamer, Davidson H.; Wylie, Blair J.
Abstract : Background: Conventional microscopy underestimates the burden of malarial infection when compared with molecular diagnosis using polymerase chain reaction (PCR)-based methods. Lower density parasitemias serve as a reservoir for infection. We evaluated the prevalence of submicroscopic infections in an area of unstable malarial transmission in India and determined whether these infections negatively impacted maternal or fetal outcomes. Methods: This cross-sectional study (2007–2008) was undertaken in two districts of Chhattisgarh, recruiting women from both antenatal clinics (ANCs) and delivery units (DUs). For ANC/DU subjects, peripheral/placental blood, respectively, was obtained for conventional microscopy and collected onto filter paper for PCR analysis. Results: There were 3425 pregnant women, including 2477 ANC subjects and 948 DU subjects who had both microscopic and PCR samples available. Polymerase chain reaction detected significantly more Plasmodium infections than traditional light microscopy both from peripheral (3·4 vs 1·2%; OR 2·9, 95% confidence intervals (CIs) 1·9–4·5) and placental (4·2 vs 1·7%; OR 2·5, 95% CIs 1·4–4·8) blood samples. Submicroscopic infections were not associated with anemia or severe maternal anemia among ANC or DU participants and were not associated with low birth weight (LBW) among DU participants. In contrast, microscopically detected infections were associated with severe anemia and LBW. Conclusions: In this area of unstable malarial transmission from India, submicroscopic infections did not identify a set of pregnant women at increased risk for anemia or LBW. Until PCR techniques become much less expensive and available as a point of care test for the field setting, its use will be limited for malarial detection.